Bahasa Indonesia Bahasa Indonesia - Viski Fitri Hendrawan; Galuh Candra Agustina; Yudit Oktanella; Aulia Firmawati; Dewi Mariyam (Postgraduate, University of Mataram, 2023)
The issue plaguing the dairy cattle industry as a whole is low reproductive efficacy due to nutritional and reproductive disorders. To overcome this, nutrients in feed play a very important function. Feed is an essential component of any livestock operation. The requirements for animal protein depend on physiological status and production level. Ruminants can also reduce protein loss by recycling urea, a normally excreted byproduct of protein metabolism. Insecticides are components of pesticides used to kill insects. Organophosphate insecticides (OPs) are phosphate-containing insecticides. Phosphoric acid used to manufacture organophosphate insecticides. This insecticide is notorious for being the most toxic to mammals. This study seeks to determine the effect of feed-containing organophosphates on FSH and LH hormone concentrations in the blood of dairy cows. Mid-lactation For the purpose of this study, Friesian Holstein dairy cattle were divided into two experimental groups, group 1 (first ration) and group 2 (second ration). ANOVA analysis was used for statistical analysis.